Dynamic simulation model for long term comprehensive environmental analysis of GAP - Saysel, Ali Kerem. (Thesis (Ph.D.)- Bogazici University. Institute of Environmental Sciences, 1999., 1999)
Integrated development projects based on water resources development, aiming hydropower production and agricultural modernization have many potential impacts on social and natural environments. Southeastern Anatolian Project (GAP), located in Southeast Turkey, comprising 10% of Turkish lands, targeting irrigation schemes on 1.7 million hectare fertile lowlands and 7400 MW hydropower production on Euphrates and Tigris would have many social and environmental consequences. In this study, potential environmental problems suggested by GAP, questions related with utilization of water resources, land degradation, agricultural pollution and land use are analyzed in systems perspective, focusing on the integrity of environmental, social and economic issues. With this aim, GAP S 1M, a dynamic simulation model is developed to trace long term trajectories of selected parameters, representing the relevant aspects of GAP's social, economic and natural environment. Based on a "systemic" problem definition, GAPSIM simulates the development rate of irrigation schemes, hydropower production with respect to changing irrigation releases, water availability on farmlands, crop selection and production, salinization, erosion, pesticide and fertilizer consumption, rangeland and forest quality, urbanization and population dynamics in GAP during 1990-2030 period, which comprises water facilities construction process. GAPSIM is validated, first "structurally", according to the validation tests suggested by the literature and then, model "behavior" is calibrated with respect to data available for the period 1990-1998. GAPSIM provides a dynamic simulation platform where several scenarios and policy analyses concerning GAP environment can be executed in order to arrive at an improved understanding of GAP as a socio-environmental system. Scenario and policy runs on GAPSIM reveal that, increased intensity of the most evapotranspirant crop cotton on GAP fields may cause significant water scarcity, which hinders the development rate of irrigation into new acres and inhibits crop yields by decreased water delivery to individual farms.
Keywords: Natural resources.; Conservation of natural resources.; Land use.